Maintenance of serum potassium with sodium zirconium cyclosilicate (ZS‐9) in heart failure patients: results from a phase 3 randomized, double‐blind, placebo‐controlled trial. (16th June 2015) - Anker, Stefan D.; Kosiborod, Mikhail; Zannad, Faiez; Piña, Ileana L.; McCullough, Peter A.; Filippatos, Gerasimos; van der Meer, Peter; Ponikowski, Piotr; Rasmussen, Henrik S.; Lavin, Philip T.; Singh, Bhupinder; Yang, Alex; et al.
Abstract : Aims: Hyperkalaemia in heart failure patients limits use of cardioprotective renin–angiotensin–aldosterone system inhibitors (RAASi). Sodium zirconium cyclosilicate (ZS‐9) is a selective potassium ion trap, whose mechanism of action may allow for potassium binding in the upper gastrointestinal tract as early as the duodenum following oral administration. ZS‐9 previously demonstrated the ability to reduce elevated potassium levels into the normal range, with a median time of normalization of 2.2 h and sustain normal potassium levels for 28 days in HARMONIZE—a Phase 3, double‐blind, randomized, placebo‐controlled trial. In the present study we evaluated management of serum potassium with daily ZS‐9 over 28 days in heart failure patients from HARMONIZE, including those receiving RAASi therapies. Methods and results: Heart failure patients with evidence of hyperkalaemia (serum potassium ≥5.1 mmol/L, n = 94) were treated with open‐label ZS‐9 for 48 h. Patients ( n = 87; 60 receiving RAASi) who achieved normokalaemia (potassium 3.5–5.0 mmol/L) were randomized to daily ZS‐9 (5, 10, or 15 g) or placebo for 28 days. Mean potassium and proportion of patients maintaining normokalaemia during days 8–29 post‐randomization were evaluated. Despite RAASi doses being kept constant, patients on 5 g, 10 g, and 15 g ZS‐9 maintained a lower potassium level (4.7 mmol/L, 4.5 mmol/L, and 4.4 mmol/L, respectively) than the placebo group (5.2 mmol/L; P <0.01 vs. each ZS‐9 group); greater proportions of ZS‐9 patients (83%, 89%, and 92%, respectively) maintained normokalaemia than placebo (40%; P < 0.01 vs. each ZS‐9 group). The safety profile was consistent with previously reported overall study population. Conclusion: Compared with placebo, all three ZS‐9 doses lowered potassium and effectively maintained normokalaemia for 28 days in heart failure patients without adjusting concomitant RAASi, while maintaining a safety profile consistent with the overall study population.